2018
DOI: 10.26508/lsa.201800036
|View full text |Cite
|
Sign up to set email alerts
|

Serine catabolism is essential to maintain mitochondrial respiration in mammalian cells

Abstract: Mitochondrial respiratory complex assembly requires the one-carbon unit generated from serine catabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
57
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 46 publications
(74 reference statements)
6
57
0
Order By: Relevance
“…Previous studies have emphasized that serine availability is critical for the maintenance of cellular anti‐oxidative capacity and mitochondrial function in cancer cells . Recently, studies further suggested that de novo serine synthesis and serine catabolism also play important roles in maintaining cellular redox balance and mitochondrial respiration in normal mammalian cells . These studies mostly focused on the role of serine in metabolism such as support of de novo ATP synthesis and provision of the one‐carbon unit.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have emphasized that serine availability is critical for the maintenance of cellular anti‐oxidative capacity and mitochondrial function in cancer cells . Recently, studies further suggested that de novo serine synthesis and serine catabolism also play important roles in maintaining cellular redox balance and mitochondrial respiration in normal mammalian cells . These studies mostly focused on the role of serine in metabolism such as support of de novo ATP synthesis and provision of the one‐carbon unit.…”
Section: Discussionmentioning
confidence: 99%
“…4,10 Recently, studies further suggested that de novo serine synthesis and serine catabolism also play important roles in maintaining cellular redox balance and mitochondrial respiration in normal mammalian cells. 3,12 These studies mostly focused on the role of serine in metabolism such as support of de novo ATP synthesis and provision of the one-carbon unit. In our study, we found that serine deficiency exacerbated oxidative stress and cellular apoptosis in IPEC-J2 cells under oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the above observations ( 73 , 77 ) that loss of SHMT2 leads to defective mitochondrial translation in cells, another study argued that the ability of an SHMT2-knockout 293A cell line to synthesize mitochondria-encoded proteins was not impaired when compared with the wild-type cells as determined using stable-isotope labeling ( 74 ). Instead, this study demonstrated that the regulation of the OXPHOS system by SHMT2 may take place after the translation of mtDNA-encoded proteins.…”
Section: Intracellular Compartmentalization Of One-carbon Metabolismmentioning
confidence: 95%
“…Recent studies have shown that mitochondrial FOCM enzymes are particularly strongly upregulated in proliferating lymphocytes and human cancers ( 17 , 69 71 ), which, in part, reflects the role of mitochondrial FOCM in supporting critical cellular functions such as cell proliferation and mitochondrial respiration. Some mitochondrial compartment–specific uses of mitochondrial folate one-carbon units include the local biosynthesis of dTTP ( 20 ) and of N -formylmethionine (fMet) ( 72 ), tRNA modification ( 73 ), oxidative phosphorylation (OXPHOS) complex assembly ( 74 ) and redox state regulation ( 75 , 76 ).…”
Section: Intracellular Compartmentalization Of One-carbon Metabolismmentioning
confidence: 99%